The effect of soil type and concrete grade on the amount of steel reinforcement used for seismic design of multipurpose hall - Nur Izzati Aliah, Azman (2019)
Multipurpose Hall is a public place where people use the space for various purposes. It also can be use as temporary place for shelter if any disaster happens, especially in case of earthquake disaster. Although, Malaysia is not located in the specific ring of fire, but that does not mean Malaysia is totally safe from earthquake disaster. Hence, temporary shelter is very important to be built and designed with strong and fit structure component to withstand the force from the ground shaking. Most buildings in Malaysia do not practice seismic design on buildings. This is a very alarming cases for local authorities like Public Works Department (JKR). Public buildings like Multipurpose Halls is very important to ensure the safety of the structure building in order for it to act as a temporary shelter for the use of civilians when earthquake occurs in Malaysia. The objective of this research is to determine the effect of soil type and concrete grade on the amount of steel reinforcement required. In addition, this project research is based on parameter of type of soil and concrete grade involving 12 building models. The 12 building models using two different parameters is used for analysis. The two parameters are Soil Type A, B, C, D, and E and Concrete Grade 25 and Concrete Grade 35. All 12 building models are based on Eurocode 8 and analyzed using Tekla Structural Software. Model of building used is 3-storey of Multipurpose Hall with height of 4.0m for each floor and 40.0m length with width of 24.0m for 12 buildings model respectively. The building models is designed by using Tekla Structural Software. The area for each floor of the Multipurpose Hall is 960 square meter. Two dimension of beam is used in the design which are 300mm x 500mm and 300mm x 600mm by using concrete beam while dimension of column is 500mm x 500mm for all column size. The material of column used is also concrete. In addition, the thickness of slab used for all floor is 250mm. The building model is considered as low rise since it is less than 6 stories according to Bureau of Planning and Sustainability, 2013. The level of 3-storey is suitable for multipurpose hall building function as hall itself and also as immediate disaster relief shelter. This Multipurpose Hall is assumed to be located in Kundasang, Sabah. All the analysis result is mostly interpreting in term of graph and Design Response Spectrum also has been discussed in the thesis. Based on the result, it can be concluded that soft soil and low concrete grade required higher amount of steel reinforcement. Multipurpose Hall designed on Soil Type D has the highest total amount of steel with the percentage of 59% compared to multipurpose hall designed based on non-seismic design. In the other hand, Concrete Grade 25 has higher total amount of steel compared to concrete grade 35 with the difference of 18%. Conclusion that can be made is both parameter play a crucial role in designing seismic building in Malaysia.